2020
DOI: 10.20944/preprints202001.0358.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential Natural Compounds for Preventing SARS-CoV-2 (2019-nCoV) Infection

Abstract: SARS-CoV-2 (2019-nCoV), a novel coronavirus, caused the pneumonia outbreak in China and continue to expand. The host receptor for 2019-nCoV Angiotensin-converting enzyme 2 (ACE2), is the same as the host receptor for SARS-CoV. Targeting ACE2 holds the promise for preventing and inhibiting 2019-nCoV infection. Chinese Medicine herbs could be a valuable pool for identifying active compounds for treating infection of 2019-nCoV. In this study, we summarize several active compounds, including baicalin, Scutellarin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
171
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(181 citation statements)
references
References 16 publications
3
171
1
6
Order By: Relevance
“…The For ACE2 target, although several compounds could bind with ACE2 through virtual screening in our studies, no compound was found to bind with the contact surface of ACE2-Spike complex, suggesting that these compounds are only the inhibitors of ACE2 enzyme activities, rather than inhibitors of ACE2 driven virus infections. Just like what described in recently published research 53 , most of selected compounds are also unable to bind with the contact surface of ACE2-Spike complex. Actually, these potential ACE2…”
Section: Discussionsupporting
confidence: 58%
“…The For ACE2 target, although several compounds could bind with ACE2 through virtual screening in our studies, no compound was found to bind with the contact surface of ACE2-Spike complex, suggesting that these compounds are only the inhibitors of ACE2 enzyme activities, rather than inhibitors of ACE2 driven virus infections. Just like what described in recently published research 53 , most of selected compounds are also unable to bind with the contact surface of ACE2-Spike complex. Actually, these potential ACE2…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, high doses of glycyrrhizin have been used in clinical trials and the compound was reported to be clinically effective for the treatment of SARS at that time [110 , 111] . Recently, glycyrrhizin was predicted to have the ability to bind ACE2 with potential anti-COVID-19 effects [112] . Hesperetin, a well-known traditional Chinese medicine, is a natural predominant flavonoid found in citrus fruits.…”
Section: Chinese Medicinementioning
confidence: 99%
“…Hesperetin dosedependently suppresses the cleavage activity of the 3C-like protease (3CLpro) of SARS-CoV in cell-free and cell-based assays [113] . Hesperetin was also reported to have the potential to inhibit ACE2 and therefore block infection with SARS-CoV-2 [112] . Baicalin, another traditional Chinese herbal medicine, is a flavone isolated from Scutellaria baicalensis .…”
Section: Chinese Medicinementioning
confidence: 99%
“…JID: ANTAGE [m5G; April 11, 2020;23:32 ] a potential strategy. Chen and Du used molecular docking to find natural compounds and proposed five candidates, including scutellarin, baicalin, hesperetin, nicotianamine and glycyrrhizin, that were potential compounds targeting the ACE2 receptor and exerting an antiviral effect to prevent SARS-CoV-2 infection [96] .…”
Section: Article In Pressmentioning
confidence: 99%